A novel experimental model of acute respiratory distress syndrome in pig - Otáhal, M; Mlček, M; Vítková, I; Kittnar, O (Physiological research, 2016)
Acute respiratory distress syndrome (ARDS) is severe medical condition occurring in critically ill patients and with mortality of 33-52 % is one of the leading causes of death in critically ill patients. To better understand pathophysiology of ARDS and to verify novel therapeutical approaches a reliable animal model is needed. Therefore we have developed modified lavage model of ARDS in the pig. After premedication (ketamine and midazolam) 35 healthy pigs were anesthetized (propofol, midazolam, morphin, pipecuronium) and orotracheally intubated and ventilated. Primary ARDS was induced by repeated cycles of lung lavage with a detergent Triton X100 diluted in saline (0.03 %) heated to 37 °C preceded by pre-oxygenation with 100 % O(2). Single cycle included two subsequent lavages followed by detergent suction. Each cycle was followed by hemodynamic and ventilation stabilization for approx. 15 min, with eventual administration of vasopressors according to an arterial blood pressure. The lavage procedure was repeated until the paO(2)/FiO(2) index after stabilization remained below 100 at PEEP 5 cm H(2)O. In 33 pigs we have achieved the desired degree of severe ARDS (PaO(2)/FiO(2)<100). Typical number of lavages was 2-3 (min. 1, max. 5). Hemodynamic tolerance and the need for vasopressors were strongly individual. In remaining two animals an unmanageable hypotension developed. For other subjects the experimental ARDS stability was good and allowed reliable measurement for more than 10 h. The present model of the ARDS is clinically relevant and thus it is suitable for further research of the pathophysiology and management of this serious medical condition.
Keywords: Disease Models, Animal; Swine; prasata; modely nemocí na zvířatech; ženské pohlaví; zvířata; plíce; Bronchoalveolar Lavage; syndrom dechové tísně; Respiratory Distress Syndrome; Female; Sus scrofa; Lung; bronchoalveolární laváž; Animals